2010
DOI: 10.1213/ane.0b013e3181b11289
|View full text |Cite
|
Sign up to set email alerts
|

Response Surface Model Predictions of Emergence and Response to Pain in the Recovery Room

Abstract: Introduction Sevoflurane - remifentanil interaction models that predict responsiveness and response to painful stimuli have been evaluated in patients undergoing elective surgery. Preliminary evaluations of model predictions were found to be consistent with observations in patients anesthetized with sevoflurane, remifentanil and fentanyl. The present study explored the feasibility of adapting the predictions of sevoflurane-remifentanil interaction models to an isoflurane-fentanyl anesthetic. We hypothesized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…42 This is supported by a study revealing that 50% of the subjects undergoing fentanylisoflurane anaesthesia woke within 2 min of the time predicted by extrapolation from a sevoflurane-remifentanil model-predicted wake-up time, on the basis of equivalence. 93 More recently, a study showed accurate predictions for wake-up time from a sevoflurane-remifentanil interaction model adapted to equipotent sufentanil-desflurane doses that were used. 94…”
Section: Volatile Anaesthetic-opioid Interactionsmentioning
confidence: 99%
“…42 This is supported by a study revealing that 50% of the subjects undergoing fentanylisoflurane anaesthesia woke within 2 min of the time predicted by extrapolation from a sevoflurane-remifentanil model-predicted wake-up time, on the basis of equivalence. 93 More recently, a study showed accurate predictions for wake-up time from a sevoflurane-remifentanil interaction model adapted to equipotent sufentanil-desflurane doses that were used. 94…”
Section: Volatile Anaesthetic-opioid Interactionsmentioning
confidence: 99%
“…A surface will encompass the complete set of isobolograms, concentration–effect curves, and curve shift effects. The RSMs are most often used clinically to predict wake up time, 1 , 18 , 19 tolerance to stimuli, 20 22 or occurrence of side effects. 1 , 23 We can help define the optimal dosing regimen by analyzing different but relevant surfaces simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…The numbers in the circles represent the number of minutes above a 95% probability of no response to laryngoscopy. To simplify presentation, fentanyl was converted to remifentanil equivalents using standardised opioid equivalency ratios . No response to laryngoscopy was defined as no movement, and no haemodynamic response in heart rate or blood pressure to direct laryngoscopy.…”
Section: Inductionmentioning
confidence: 99%
“…The time window presented starts 50 min into the anaesthetic to 20 min after the anaesthetic is turned off. Isoflurane and fentanyl simulations were performed using published pharmacokinetic and pharmacodynamic models . Definitions, simulated patients’ characteristics, assumptions and limitations are presented below Table .…”
Section: Emergencementioning
confidence: 99%
See 1 more Smart Citation